2019
DOI: 10.3802/jgo.2019.30.e62
|View full text |Cite
|
Sign up to set email alerts
|

Conservative hysteroscopic treatment of stage I well differentiated endometrial cancer in patients with high surgical risk: a pilot study

Abstract: Objective To report hysteroscopic treatment combined with levonorgestrel-releasing intrauterine device (LNG-IUD) to treat women with early well differentiated endometrial cancer (EC) at high surgical risk. Methods Nine women diagnosed with stage IA, grade 1 endometrioid EC which was contraindicated or refused standard treatment with external beam radiation therapy with or without brachytherapy were enrolled in our prospective study. Endo-myometrial hysteroscopic resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
1
13
2
Order By: Relevance
“…These outcomes are similar to those reported in the literature and show the efficacy of progestin therapy in superficial pre-neoplastic lesions [13,18]. Our study showed a complete remission at the first control in 94.4% of cases diagnosed with G1 EEC undergoing combined therapy and this finding agrees with those of other studies that indicated a response rate between 78% and 100% [6,7]. In our study, the cases of recurrence are slightly higher than those reported by Giampaolino et al [6], likely because we carried out a longer follow-up and included women with minimal myometrial infiltration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These outcomes are similar to those reported in the literature and show the efficacy of progestin therapy in superficial pre-neoplastic lesions [13,18]. Our study showed a complete remission at the first control in 94.4% of cases diagnosed with G1 EEC undergoing combined therapy and this finding agrees with those of other studies that indicated a response rate between 78% and 100% [6,7]. In our study, the cases of recurrence are slightly higher than those reported by Giampaolino et al [6], likely because we carried out a longer follow-up and included women with minimal myometrial infiltration.…”
Section: Discussionsupporting
confidence: 92%
“…These data highlight the importance of preserving fertility in these young women. The conservative management of early stage EC is generally well-accepted in young women wishing to preserve their fertility or in women who have severe surgical risk factors [6,7]. In fact, hysteroscopic resections accompanied by hormonal therapy for fertility-sparing treatment in young women with early-stage EC were reported in several studies [6,8,9], and it appears to be a reasonable opportunity in these cases with specific criteria.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are often dosimetric and technical difficulties, which means that radiotherapy cannot be used. Therefore, there is a great need to search for therapeutic methods for women at high surgical risk [23].…”
Section: Discussionmentioning
confidence: 99%
“…5ALA: 5-aminolevurinic acid, PDD: photodynamic diagnosis. vice (LNG-IUD), due to surgical intolerance preventing a radical operation [13].…”
Section: Discussionmentioning
confidence: 99%